صورة التدين الوسط في القرآن الكريم: دراسة وصفية Image of Moderate Religiosity in the Qur’an: A Descriptive Study - (Musaddiq Majid Khan), مصدق مجيد خان; (Israr Ahmad Khan), إسرار أحمد خان (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
الملخص تعنى هذه الدراسة ببيان معنى التدين الوسط بالاعتماد على آي الذكر الحكيم التي اهتمت بوضع صورة غاية في الوضوح لمفهوم التدين الوسط الذي لا مغارة فيه ولا تفريط. فالوسطية من نعم الله تعالى التي أنعم بها على الأمة الإسلامية والتي شرفهم بها هي أن الله تعالى جعلها أمة وسطًا، خيارًا وعدولًا، وأخرجها للناس، وقد شهد لها القرآن الكريم بذلك. ولكن بعد القرون المشهودة بالخير ظهر التفرق والاختلاف، فخرجت بعض الفرق ببدعها، وظهرت بغلوها وفتنها، ثم تواصل ظهور البدع، وتوارثت الأجيال كثيرًا من الانحرافات العقدية والعملية، وابتعدت عن منهج الاعتدال والتوسط الذي رسمه القرآن الكريم. وقد وظّف الباحث المنهج الوصفي لمعرفة منهجية القرآن في التدين، ببيان معنى الوسطية في القرآن في الإيمان بالله، وملائكته، وكتبه، ورسله، واليوم الآخر والقضاء والقدر كما أنه تعرض لذكر نماذج من التدين المنحرف في القرآن الكريم سواء اكان بسبب المغالاة أم التفريط حتى نكون على بيّنة من التدين الوسط. الكلمات المفتاحية: القرآن الكريم، التدين، الوسط، النواميس العقدية، القواعد العملية. ******************************************* Abstract This study is concerned with the meaning of moderate religiosity based on the verses of the Holy Qur’an, which focus on the development of a very clear concept of moderate religiosity without any obscurity and confusion. Moderation is one of the favors of Allah which He bestowed upon the Muslims and honored them as He made them the best, just, moderate nation as mentioned in the Qur’an. But after many graceful centuries, dispersions and differences appeared as many sects emerged with innovations, exaggerations, and tempting incitements. The emergence of innovations continued and hence generations of people inherited a lot of cardinal and practical deviations and thus moved away from the moderate approach as charted by the Qur’an. The researchers used descriptive method to study the Qur’anic approach regarding religiosity by explaining the meaning of the moderation in the Qur’an regarding the faith in Allah, His angels, His books, His Messengers, the Last Day, and fate and destiny . In addition to that the researchers mentioned some examples of deviant religiosity as recorded in the Qur’an whether it is because of exaggeration or excessiveness so as to be clear about moderate religiosity. Keywords: The Qur’an, Religiosity, Middle, Cardinal Beliefs, Practical Rules.